Correlation Analysis of ISO 25010 Modularity, CK Metrics, and Architecture Smells - Maulana Alirridlo; Enrico Almer Tahara; Siti Rochimah (Ikatan Ahli Informatika Indonesia (IAII), 2025)
Open-source software projects face increasing challenges in maintaining design quality as they evolve, often resulting in technical debt accumulation and reduced maintainability. This study explores the relationship between software modularity, measured using ISO/IEC 25010 quality attributes, Chidamber and Kemerer (CK) object-oriented metrics, and architectural smells (AS) in Java-based open-source software. Six Java-based open-source projects were strategically selected based on varying complexity levels (ranging from 6-994 classes) and different application domains to ensure comprehensive analysis coverage using DesigniteJava to extract AS, CK metrics, and modularity indicators. Correlation analyses showed that architectural smells such as Cyclic Dependency, Ambiguous Interface, and God Component are strongly correlated with CK metrics like Weighted Methods per Class, Depth of Inheritance Tree, and Number of Children. These CK metrics also exhibited strong positive correlations with Cyclomatic Complexity, indicating that structurally complex components also tend to have more complex control logic. Dense Structure was found to negatively correlate with Coupling of Components Conformance, suggesting its effect on modularity compliance. On the other hand, smells like Feature Concentration and Scattered Functionality showed weak or inconsistent correlations with these metrics. The findings highlight the importance of addressing specific architectural smells to improve modularity and software quality.